Geospatial intelligence origins and evolution - Clark, Robert M. (Georgetown University Press, 2020)
"This book introduces readers to the development of geospatial intelligence (GEOINT), the convergence of the disciplines of geography, geographical information systems (GIS), and remote sensing with intelligence. The book begins with GEOINT's roots in ancient mapping and navigation and continues to the present when we carry our geospatial knowledge around with us in our smartphones, automobiles, and wristwatches. GEOINT, simply put, is the determination, depiction, analysis, and use of an object's location on earth. First developed in the national security community, it has become integral to the work of other government agencies, NGOs, and corporations. It has myriad commercial and scientific applications. "Geospatial Intelligence" weaves a tapestry of stories about the people, events, and ideas that have shaped the trajectory of geospatial intelligence. The final chapter peers into likely future applications. The book is well suited as a primary text and/or as supplemental reading for undergraduate- and graduate-level courses on geospatial intelligence, homeland security, geography, and in related geophysical disciplines."
Keywords: Geschichte; Geoinformationssystem; Digitale Karte; Raumdaten; Geographic information systems; Geospatial data; Digital mapping; Intelligence service / United States; Intelligence service; United States